2000
DOI: 10.1002/hep.510310214
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes of fibrinolysis in patients with liver cirrhosis and esophageal varices

Abstract: Variceal bleeding, whose triggering mechanisms are largely unknown, occurs with a circadian rhythmicity, with 2 peaks, one greater, in the evening, and one smaller, in the early morning. We assessed some clotting and hemodynamic parameters, possibly involved in variceal hemorrhage, over a 24-hour period, at 4-hour intervals, in 16 patients with cirrhosis and esophageal varices and in 9 controls. At each time interval, tissue plasminogen activator (tPA) and tPA inhibitor-1 (PAI-1) antigens and activities and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…[8]. This was first suggested by the study by Vinel et al [9], showing a relationship between portal [16,17]. Although …”
Section: Moreover Over 90 % Of the Patients In Whom The Acute Bleementioning
confidence: 77%
See 1 more Smart Citation
“…[8]. This was first suggested by the study by Vinel et al [9], showing a relationship between portal [16,17]. Although …”
Section: Moreover Over 90 % Of the Patients In Whom The Acute Bleementioning
confidence: 77%
“…L'augmentation de fr6quence de l'hyperfibrinolyse, de troubles du thrombo-61estogramme, li6e h la pr6sence d'infections et/ou d'h6morragie variqueuse a 6t6 rapport6e [16,17]. Bien que dans le pass6, on ait accord6 peu d'attention ~ ces facteurs, la disponibilit6 de m6dicaments qui peuvent am61iorer de fa~on significative et rapide le profil de coagulation des patients porteurs de cirrhose a permis de noter maintenant un regain d'int6r~t darts ce domaine.…”
Section: Predictors Of Esophageal Variceal Hemorrhageunclassified
“…This may due to the particular in vitro assay used. In contrast, in vivo correlation between hyperfibrinolysis and an increased risk of variceal bleeding, compatible with the circadian rhythm of hyperfibrinolytic activity has been shown [83]. In addition, increased fibrinolytic activity during liver transplantation and hepatic resection correlates with blood loss [84].…”
Section: Disorders Of the Fibrinolytic Systemmentioning
confidence: 90%
“…In a prospective study, it was demonstrated that patients with positive fibrinogen degradation products or class C had a significantly higher risk of gastrointestinal bleeding [24]. Moreover, it has been demonstrated that fibrinolysis follows a circadian rhythm in cirrhosis, whose temporal distribution coincides with episodes of variceal bleeding, suggesting a possible role of hyperfibrinolysis in the variceal hemorrhage [30].…”
Section: Variceal Bleedingmentioning
confidence: 99%